Forensic Identification of Fentanyl and its Analogs by Electrochemical-Surface Enhanced Raman Spectroscopy (EC-SERS) for the Screening of Seized Drugs of Abuse - Ott, Colby E.; Perez-Estebanez, Martin; Hernandez, Sheila; Kelly, Kendra; Dalzell, Kourtney A.; Arcos-Martinez, M. Julia; Heras, Aranzazu; Colina, Alvaro; Arroyo, Luis E. (Frontiers in Analytical Science, 2022)
Reliable identification of fentanyl and fentanyl analogs present in seized drug samples is imperative to the safety of first responders and laboratory personnel and informs the future analysis process and handling procedures. The electrochemical-surface enhanced Raman spectroscopy (EC-SERS) method developed in this work allows the in-situ preparation of the SERS substrate providing a rapid, efficient, and accurate approach to detect fentanyl, even at low percent by weight concentrations common in seized drugs. Optimization of the electrochemical potentials suitable for the SERS substrate preparation and adsorption of the analyte was achieved using multi-pulse amperometric detection. This method demonstrated large enhancement of the SERS response. This method was applied to six fentanyl analogs with substitutions to the amide group, representing small changes in the fentanyl core structure. Identification of these analogs through differences in the EC-SERS spectra was evident. Interference studies incorporating analytes frequently encountered with fentanyl including heroin, cocaine, methamphetamine, naltrexone, and naloxone were assessed and found to offer limited to no interference. The limits of detection of the fentanyl compounds were in the low to mid nanograms per milliliter range, with the most sensitive compound detected at 10 ng/ml. Application of the method to simulated drug mixtures was performed to determine fit-for-purpose. In all mixtures with fentanyl as the minor contributor, fentanyl was correctly identified, including mixture samples comprised of 5 and 1% fentanyl. This approach represents the first in-situ EC-SERS analysis of fentanyl and its analogs and provides accurate and efficient screening for fentanyl in seized drug samples.